Implementasi Game Educaplay untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Keragaman Budaya Indonesiaku di Kelas 5 SDN Banjaran 4 - Taurista, Pungky Selvia; Dewi, Lusi Noviana; Romadhoni, Alifvia Novita Putri; Sofiana, Mirza Sheila; Zuroida, Dzulhijatul Awalin; Rahayu, Anik Puji; Primasatya, Nurita (Universitas Nusantara PGRI Kediri, 2024)
This study aims to implement educaplay as an educational game used as a learning medium to improve students' learning outcomes on the topic